Devianza di gender nella commedia e nella cultura del cinquecento italiano - Giannetti, Laura (Acta Histriae, 2007)
This article examines early modern cultural meanings of gender deviance and sex transformations looking at historical evidence and literary productions such as narratives by humanistic writers, comedies, poetry and medical texts. It argues that issues of masculine identity, male cross-dressing and gender deviance - in their different representations - are closely connected to a 'discourse' on the sexual status of young males in sixteenth-century Italy. It aims at showing that male gender and sexual inversion - in literature as well as in everyday life - could be tolerated if it fit into the commonly accepted sexual and gender hierarchy of the time
Keywords: 16.st.; deviantnost; komedija; spol; spolna identiteta; travsetija